(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
This study is about a selection of excerpts of text which there is not official publication of course ministered by B. F. Skinner in 1947 a respect of verbal behavior. The manuscript have historical importance because contains the skinnerian’s approach of verbal behavior ten years before the official publication of the book “Verbal Behavior”. The manuscript was elaborated by Ralph Hefferline, who was Colúmbia University`s professor, where Skinner offer your course. For selection of excerpts transcribed in this study the authors choose two important topics for comprehension of verbal behavior : (1) meaning and (2) definition of verbal behavior.